Inter-comparison of transboundary atmospheric dispersion calculations: A summary of outputs from the ASEAN NPSR benchmark exercise. (May 2021) - Silva, Kampanart; Krisanungkura, Piyawan; Khunsrimek, Narakhan; Vechgama, Wasin; Hao, Tang Jia; Krishnan, Vitesh; Long, Pham Kim; Charnock, Tom; Rassame, Somboon; Kiat, Tay Bee; Yeow, Chung Keng; Than, Hoang Sy; et al.
Abstract: Previous nuclear power plant (NPP) severe accidents have raised great concern in Southeast Asia on the issue of transboundary atmospheric dispersion of an accidental release from an external NPP. This study presents the inter-comparison of atmospheric dispersion calculations performed by different calculation codes employing Lagrangian particle model or Gaussian puff model with Southeast Asia weather data during the northeast monsoon period. The test case is a hypothetical accident in Fangchenggang NPP with a hypothetical source term. Radionuclide concentration and radiation dose distribution maps along with specified values at specific locations are compared to demonstrate the similarities and differences of each calculation code. All calculation codes can generally capture the dispersion pathway, though only those employing Lagrangian particle model can record microscale changes in wind direction. Analysis of predicted exposure extent and lead time shows that radioactive plume contributing to the radiation dose of several μSv/day can reach one or more ASEAN countries within the 24-h timeframe. This information can be used to design appropriate risk communication strategy to dispel unnecessary public anxiety or to plan for more extensive radiation monitoring capability. For this purpose, Gaussian puff model can be used to provide initial information which can be later confirmed by Lagrangian particle model. Highlights: Transboundary atmospheric dispersion calculation is done with SE Asia weather data. Initial calculation by Guassian models can be later confirmed by Lagrangian models. Plume corresponding to 0.1 μ Sv/h from an external NPP can reach SE Asia in a day. This information helps design risk communication and radiation monitoring strategies.